CO2 sequestration with enhanced shale gas recovery. Issue 24 (17th December 2021) - Liu, Danqing; Li, Yilian; Yang, Seng; Agarwal, Ramesh K.
ABSTRACT: CO2 enhanced shale gas recovery has the merits of both increasing the natural gas production to address the global energy crisis as well as simultaneously the geological storage of CO2 to reduce the anthropogenic greenhouse gas emissions. Although it has huge development potential and wide application prospects, this technology is still in a very preliminary stage of deployment. The research status of the CO2 enhanced shale gas recovery is summarized in this paper in order to stimulate further research and development in this field worldwide to address the dual problem of energy crisis and environmental degradation.